Covid-19 Pandemic and the Protection of Older People in International Comparison. Results of Comparative Research from an Ethical Perspective - Forster, Sophia; Frewer, Andreas (Pandemics and Ethics, 2023)
The corona pandemic affects older people in particular: isolation and quarantine in the lockdown, strict visiting regulations in institutions, etc. The protection of the well-being threatened by a Covid-19 infection is to be ensured above all by restricting social contacts. However, regular interpersonal meetings are also a relevant protective factor for physical and mental health. Strict visiting bans are an extreme psychological burden, especially for residents of nursing homes, as the affected people were neither involved in the underlying decision-making process nor were able to resist the resulting regulations. Thus, many residents reacted to the measures taken with incomprehension and rejection. In the following, the course of the pandemic will first be set in a global context from the perspective of Germany (2). Subsequently, central topics will be illuminated which contain particular relevance and ethical brittleness in the question of the protection of older groups of people (2.1–2.4). This will be followed by a detailed comparison of the situation in nursing and old people’s homes in different countries in order to gain an orientation about the local situation there (3.1–3.2). The results of the analysis also reveal potential sources of error in international comparisons. Finally, a comprehensive principles reflection rounds off the contribution (4) and central final considerations give an outlook on the still dynamic course of events (5).
CRIS-Team Scopus Importer:2024-06-28